The long-term ecology of the lost forests of La Laguna, Tenerife (Canary Islands) - de Nascimento, L; Willis, K; Fernández-Palacios, J; Criado, C; Whittaker, R (Blackwell Publishing Ltd., 2009)
Aim: We report the first analysis of the long-term ecology of Tenerife, in order to establish a pre-colonization base-line and to assess the effect of human activity and the role of climatic variation on vegetation during the Late Holocene. Location: A former lake bed in the city of La Laguna (Tenerife, Canary Islands, Spain). Methods: A sedimentary sequence of over 2 m was obtained from the former lake bed. Fossil pollen and microfossil charcoal concentrations were analysed. Radiocarbon dating of the sequence indicates that it spans approximately the last 4700 years. The pollen diagram was zoned using optimal splitting within PSIMPOLL 4.25. Results: Three pollen zones were differentiated: (1) in Zone L1 (c. 4700-2900 cal. yr BP) a mixed forest was dominated by Quercus, Carpinus, Myrica and Pinus, (2) in Zone L2 (c.2900-2000 cal. yr BP) the laurel forest taxa increased, while Pinus, Juniperus and Phoenix declined; and (3) Zone L3 (c.2000-400 cal. yr BP) was characterized by the decline of Carpinus and Quercus and the abundance of laurel forest taxa (e.g. Myrica). Neither Carpinus nor Quercus was hitherto considered to be native to the Canary Islands. Their decline started c. 2000 years ago, coinciding with microfossil charcoal evidence of increased burning and with archaeological evidence for the first human settlement on Tenerife. Main conclusion: Between c. 4700 and 2000 cal. yr BP, the composition of the forest in the valley of La Laguna was very different from what it is at present. In particular, Quercus and Carpinus appear to have been significant components, alongside components of the present-day laurel forst, and the native pine (Pinus canariensis) forest and thermophilous woodland were also more prevalent in the region (but probably not within the lake basin itself) until 3000 cal. yr BP. The subsequent decline of Quercus and Carpinus led to the establishment of the present laurel forest in the region and a shift to more open vegetation types. These changes indicate the the aboriginal inhabitants of the islands, the Guanches, had a far more profound impact on the vegetation of Tenerife than hitherto realized.